2006
DOI: 10.1037/1099-9809.12.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Exemplary multicultural training in school psychology programs.

Abstract: This study examined the characteristics of school psychology programs noted for training students from a multicultural perspective. The program characteristics and training environment at 17 programs were studied through semistructured interviews with faculty and students, and reviews of prospective student application materials for multicultural content. Findings suggest that students at all programs were exposed to minority clients during applied fieldwork, 94% of the programs required a diversity issues cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 39 publications
2
111
0
Order By: Relevance
“…Cross-cultural competence is developed from a combination of coursework and supervised experience (Fontes & Thomas, 1996). The need to increase exposure to diverse populations has been proposed elsewhere (Rogers et al, 1992) and was supported in this study by participants' recommendations regarding how to improve cultural-diversity training. The most frequently recommended improvement for training was to increase exposure to diverse students and families during supervised clinical experiences.…”
Section: Diversity Training Among School Psychologistsmentioning
confidence: 93%
See 1 more Smart Citation
“…Cross-cultural competence is developed from a combination of coursework and supervised experience (Fontes & Thomas, 1996). The need to increase exposure to diverse populations has been proposed elsewhere (Rogers et al, 1992) and was supported in this study by participants' recommendations regarding how to improve cultural-diversity training. The most frequently recommended improvement for training was to increase exposure to diverse students and families during supervised clinical experiences.…”
Section: Diversity Training Among School Psychologistsmentioning
confidence: 93%
“…Research studying the content of school psychology training programs suggests that graduate students are not routinely exposed to significant cross-cultural school psychology courses and receive limited exposure to diverse groups during field-training experiences. In the area of graduate coursework, Rogers, Conoley, Ponterotto, and Wiese (1992) surveyed directors of school psychology programs and found that only 60% of programs offered at least one course specifically devoted to multicultural issues. Sixty-nine percent of the directors estimated that student exposure to ethnic-minority clients occurred less than one quarter of the time during practicum and internship experiences.…”
mentioning
confidence: 99%
“…The first limitation is that publications in school psychology journals are only one indicator of the extent to which diversity is incorporated into a field. Among other indicators that were not examined but are believed to be important toward promoting cultural competence among school psychologists are recruitment and retention of students and faculty from underrepresented populations (Rogers, 2005;Zhou et al, 2004), the extent to which diversity issues are incorporated into school psychology training (Rogers, 2005), diversity-related presentations at state, regional, and national conferences, diversity-related publications in other sources (e.g., professional newsletters), availability and utilization of training for cultural competency, and position statements adopted by state, national, and international organizations that represent school psychologists. Also, by not counting all studies that contained a minority sample as "diversity related," this study may have underrepresented the actual amount of research being conducted with minority students.…”
Section: Limitationsmentioning
confidence: 98%
“…Caucasian women school personnel still provide most of these services, their program directors are predominantly men, and surveys have not reported specific ethnicities for school psychology faculty and students (Reschly, 2000). Non-White membership in the National Association of School Psychologists approximates 10% (Rogers, 2005) and is somewhat below recent student/faculty percentages in all graduate programs of 27%/12% (Norcross, Kohout, & Wichierski, 2005). The continuing absence of a "critical mass" of nonWhite students and faculty in school psychology requires careful student recruitment planning to address this dilemma (Zhou et al, 2004).…”
Section: A Mental Health Model For School Psychology Practicementioning
confidence: 95%
“…Surveys of cultural competency training in school psychology have examined exemplar programs approaching critical match, incorporating multicultural perspectives in the curriculum, and endorsing strong institutional/faculty support for recruitment and retention of minority students (Rogers, 2005). Despite this research, most school psychology students still interpret bilingual assessment results without benefit of adequate training or courses relevant to minority issues.…”
Section: School Psychology Trainingmentioning
confidence: 97%